REACTUALIZATION OF MAQAMAT WAL AHWAL AS A PARADIGM OF MODERN ISLAMIC RELIGIOUS EDUCATION IN CRITICAL LITERATURE STUDY - Achmad Faqih; Jamaludin Jamaludin; Solihah Sari Rahayu (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2026)
Maqamat wal Ahwal is a central concept in Sufi thought, referring to the spiritual stations (maqamat) achieved through mujahadah and riyaḍah, and inner states (ahwal) bestowed as divine gifts from Allah SWT in the journey of a spiritual seeker (salik). In the modern era, Islamic Religious Education (PAI) faces serious challenges including moral crises, spiritual degradation, and value disorientation among youth occurring precisely amid various character strengthening programs that have been implemented suggesting that current approaches remain cognitive and normative without engaging the spiritual dimension of students. This study aims to analyze how the reactualization of maqamat wal ahwal can serve as a holistic paradigm for modern PAI capable of addressing this crisis fundamentally. The study employs a critical literature review method, analyzing thirty relevant sources published between 2020 and 2026 through content analysis and thematic synthesis. The results reveal three main findings: first, maqamat wal ahwal provides a structured spiritual pedagogical framework for modern PAI by integrating the dimensions of human striving and divine bestowal into one cohesive educational process; second, the values embedded in maqamat are proven psychologically and pedagogically relevant for character formation among Generation Z students facing the pressures of digitalization and spiritual identity crises; and third, the reactualization model of maqamat wal ahwal through the integration of takhalli, tahalli, and tajalli stages represents a holistic and measurable character-learning blueprint. This study concludes that maqamat wal ahwal is an Islamic epistemological asset that must be integrated as a transformative paradigm in modern PAI curricula, and recommends developing maqamat wal ahwal-based PAI models as a strategic response to the spiritual crisis facing young Muslims in Indonesia. Keywords: Maqamat; Ahwal; Islamic Religious Education; Sufism; Critical Literature Review